(untitled) (Bangladesh Journal of Urology, 2020)
Introduction: Renal Transplantation is the optimal treatment for end-stage renal disease.Among the surgical complication in Renal Transplant vascular complication is most dreadedand many lead to sudden allograft loss and increase patient morbidity and even mortality. Objective: To share our experience and analysis of outcome of vascular complicationsof Live related Renal Transplant in our Bangabandhu Sheikh Mujib Medical University(BSMMU), Dhaka. Materials & Methods: One hundred eighty two (182) live related Renal Transplantwere performed from July 2011 to March 2020. During this period we evaluated thiscases retrospectively to find out vascular complications and analyzed them for frequency,clinical presentation and their management and outcome. Result: The age of recipients range from 6-65 years, male 129, female 53 vascularcomplications are found in 8 cases — 1 Renal Artery Thrombosis, 2 venous thrombosis,1 Renal Artery aneurysm, 1 hematocele, 3 lymphocele. 4 patients needed graftnephrectomy, 2 lymphocele cases need lympho-peritoneal shunt and 1 improve bysclerotherapy with povidone-iodine, hematoma needs surgical evacuation. One patientdied after graft Nephrectomy due to sepsis. Conclusion: Major vascular complications are relatively uncommon after live relatedRenal Transplantation but still contributes a major factor of graft loss and patientmorbidity. According to these data we can conclude Renal Transplantation is safeprocedure for end stage renal disease. Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.72-75